Kalar1 and Kalar2, Newly Released Wheat Varieties for Cultivation under Rain-fed Conditions - Awtaq, Star Ali; Azeez, Ali Shamsullah; Mahmood, Yadgar Ali; Abdulkareem, Narmeen Rashid; Jamal, Khalil Musa (Kurdistan Journal of Applied Research, 2021)
Improving new varieties plays an important role to increase the productivity of wheat grain yield in Iraq. Garmian region as a semi-arid area is extremely suffering with low wheat yield production as a result of continuing yield potential reduction of the local cultivars over the time. This project was conducted at the Directory of Garmian Agricultural Research to develop new cultivars through four field trials from 2009 to 2013. In the selection phase, 50 lines of Facultative and Winter Wheat Observation Nurseries (16th FAWWON-IR) were screened, and three superior lines (SL1; CH75479/SARDARI-HD74, SL2; CATBERD/CNO79*2/HEF1, and SL3; ID800994.W/VEE/5/CA8055/4/ROMTAST/BON/3/DIBO//SU) to the best local check (Aras) for grain yield, thousand grain weight, anthesis date and plant height were selected for testing in three field trials of comparison phase. Averaging over years, the results of this project significantly confirmed that two of the selected lines (SL1 and SL2) performed superior (4.24 and 4.73 t h-1, respectively) to the local check (Aras; 2.83 t h-1) with regards to grain yield production by about 50-60% (P < 0.001). This superiority of the selected lines compared to the local check was due to significant longer spike through increasing grain number (P < 0.001), and wider flag-leaf area which leads to assimilate more CO2 to the grain during grain filling duration (P < 0.01). Based on these results, the superior genotypes (SL1 and SL2) were then qualified for identification and officially released (Reference Number 192, dated November 21, 2018) as new cultivars namely Kalar1 (SL1) and Kalar2 (SL2) by the National Committee for Recording and Protecting Agricultural Varieties in Iraq for the climate of Garmian region.